Dark Current Voltage Characteristics of Micromorph Silicon Tandem Cells - Sturiale, Alejandro Ernesto (2009)
The transport mechanisms controlling the forward dark current-voltage characteristic of the silicon micromorph tandem solar cell were investigated with numerical modeling techniques. The dark current-voltage characteristics of the micromorph tandem structure at forward voltages show three regions: two with an exponential dependence and a third where the current grows more slowly with the applied voltage. In the first exponential region the current is entirely controlled by recombination through gap states of the top cell. In the second exponential region the current is controlled by the mixture of recombination through gap states of both the top and bottom cells and by free carrier diffusion along the a-Si:H intrinsic layer. In the third region the onset of the electron space charge limited current on the a-Si:H top cell can be observed along with some other mechanisms that are discussed in the paper. The high forward dark J-V curve of the tandem cell can be used as diagnosis tool to quickly inspect the efficiency of the recombination junction in recombining the electron-hole pairs generated under illumination in the top and bottom cells. The dark current at high forward voltages is highly influenced by the amount of electron-hole pairs thermally generated inside the recombination junction.